Reasonability of gastro-oesophageal reflux study requests (contrast swallows and milk scans) for the detection of gastro-oesophageal reflux disease at Red Cross War Memorial Children's Hospital - a retrospective analysis - Bau, Steffen (Department of Paediatrics and Child Health, 2016)
Includes bibliographical references